P352 A propensity score-matched, real-world comparison of ustekinumab vs vedolizumab as a second-line treatment for Crohn's disease. The Cross Pennine study II. (27th May 2021) - Lenti, M V; Dolby, V; Clark, T; Hall, V; Tattersall, S; Fairhurst, F; Kenneth, C; Walker, R; Kemp, K; Borg-Bartolo, S; Limdi, J; Taylor, J; et al.
Abstract: Background: The best choice of biological agents after failure to an anti-tumour necrosis factor (TNF)α agent in patients with Crohn's disease (CD) is yet to be defined. Real-world data dealing with this issue are still emerging. Methods: This is a multicentre retrospective study including eight UK hospitals (August 2014-April 2020). We retrospectively collected data of patients treated with ustekinumab. Clinical response and remission at 14 and 52 weeks evaluated through Physician Global Assessment (PGA) and adverse events were recorded. Predictors of clinical response were examined, and a propensity score-matched analysis with a cohort of patients treated with vedolizumab was performed. Results: Overall, 282 patients (mean age 40±15, F:M ratio 1.7:1) treated with ustekinumab were included. Clinical response or remission was reached by 200/282 patients (70.9%) at 14 weeks, and by 162/259 patients (62.5%) at 52 weeks. The most common reason for discontinuation was either primary failure or loss of response, followed by the occurrence of adverse events and by the need for surgery. The rate of non-adherence was rather low (1.4%). Current smoking (OR 2.48, 95% CI 1.13-5.44; p=0.02), baseline PGA (OR 2.4, 95% CI 1.55-3.69, p<0.001), and use of steroids (OR 2.42, 95% CI 1.26-4.65, p=0.008) were associated with 52-week treatment failure. Overall, 74 adverse events occurred, of which 26 were labelled as serious (8.3 per 100 person-year). After exclusion of patients without anti-TNFα exposure prior to starting ustekinumab or vedolizumab and exclusion of patients previously exposed to vedolizumab or ustekinumab, we analysed 275/282 patients (97.5%) from the ustekinumab cohort and 118/135 patients (87.4%) from the vedolizumab cohort. Propensity score analysis revealed that at 14 weeks, patients treated with ustekinumab were 38% (95% CI 25-50%; p<0.001) more likely to achieve a clinical remission, while at 52 weeks, the difference of 9% (95% CI -15-33%; p=0.462) was not significant. Conclusion: Ustekinumab was effective and well tolerated in this real-world cohort. While ustekinumab proved more effective at 14-week follow-up, we found no statistically significant differences in outcomes at 52 weeks.